Role of progression of training volume on intramuscular adaptations in patients with chronic obstructive pulmonary disease - Nyberg, Andre; Milad, Nadia; Martin, Mickael; Patoine, Dany; Morissette, Mathieu C; Saey, Didier; Maltais, François (Frontiers in Physiology, 2022)
Introduction: Quadriceps dysfunction is a common systemic manifestation of chronic obstructive pulmonary disease (COPD), for which treatment using resistance training is highly recommended. Even though training volume is suggested to be a key explanatory factor for intramuscular adaptation to resistance training in healthy older adults, knowledge is scarce on the role of progression of training volume for intramuscular adaptations in COPD. Methods: This study was a sub-analysis of a parallel-group randomized controlled trial. Thirteen patients with COPD (median 66 yrs., forced expiratory volume in 1 second 44% predicted) performed eight weeks of low-load resistance training. In a post hoc analysis, they were divided into two groups according to their training volume progression. Fiber-type distribution and oxidative muscle protein levels, i.e., citrate synthase (CS), hydroxyacyl-coenzyme A dehydrogenase (HADH), mitochondrial transcription factor A (TfAM) as well as functional quadriceps endurance measures (total work from isotonic and isokinetic knee extension tests), were assessed before and after the intervention period. Results: The continued progression group sustained their training volume progression during weeks 5 to 8 compared to weeks 1 to 4 (median +25%), while the discontinued progression group did not (median -2%) (p=0.007 between groups). Compared with baseline values, significant between-group differences in fiber type distribution, TfAM and HADH muscle protein levels (range + 17 to 62%, p<0.05) and in individual responses to selected outcomes (median 89 vs. 50%, p=0.001) were seen in favor of the continued progression group. At the functional level, only the continued progression group had a significant increase in isotonic (+56%, p=0.004) and isokinetic (+7%, p=0.004) quadriceps endurance, but the between-group differences did not reach statistical significance (range 14-29%, p=0.330-1.000). Discussion: Continued progression of training volume after the initial weeks of training enabled larger intramuscular adaptations following low-load resistance training among patients with severe to very severe COPD. These findings provide novel insight that could be used in the design of future resistance training studies to counteract quadriceps dysfunction within the COPD population. Still, considering the small sample size and the post hoc nature of our analyses, these results should be interpreted cautiously, and further research is necessary.